FEMINISME DALAM COVER KOMIK SRI ASIH SEBAGAI KOMIK KLASIK PERTAMA INDONESIA - Diego, Diego (Fakultas Ilmu Sosial Universitas Negeri Padang, 2016)
Comic is one of the mass media product that is very popular in the 1950s. Indonesian Comic at beginning was only in form of strip comic in a newspaper and then came on demand from the public for the compiled strip comic. Then, up to the merged comic of Sri Asih, written by RA. Kosasih, and later known as the first comic indonesia which was written and painted by Indonesian native.Before the comic of sri asih arouse, the community were introduced by translated foreign comic that had been popular in their origin country.Â This research aims to define feminism originate in Sri Asih comic that described with qualitative research methodology. The comic of Sri Asih is analyzed by using Semiotics Charles Pierce which consists of sign, object and interpretation. The result showed that of abuse and violence against womens both in the verbal and nonverbal became the reason for the emergence of feminism in Sri Asih comic besides women situation that occurs in the 1950s and the publisher demands on RA Kosasih to make comic titled superheroes. This research also shows radical cultural feminism in Sri Asih comic as form of fight represented by Sri Asih in achieving the objective of gender equality between man and woman.Keywords: Feminism, Charles Pierce semiotics, Sri Asih Comics